Chemical contact tracing for exposomics. Issue 1 (20th January 2022) - Liu, Ken
Abstract: Human health and disease reflects a complex interplay between the genome and the exposome. High-resolution mass spectrometry (HRMS)-based metabolomics routinely measures thousands of endogenous, dietary and xenobiotic chemicals. However, confident identification of exposure-related chemicals remains a challenge as a significant portion of chemical signals detected in metabolomics analyses remains uncharacterized. Illuminating the "dark matter" of the exposome cannot be accomplished efficiently if the prevailing approach depends on the use of purified authentic standards that are not readily accessible for most laboratories. An alternative approach involves chemical exposure "contact tracing" analogous to contact tracing used to track the spread of infectious disease. For transmissible diseases, contact tracing identifies sets of potentially infected individuals that are linked by close contact to a confirmed positive case. Similarly, chemical exposures can be identified by establishing sets of xenobiotic metabolites that are linked to the original exposure via enzymatic biotransformation. Here, we provide a commentary on how incorporating enzyme-based strategies for chemical contact tracing enables -omics scale characterization of chemical exposures to further illuminate the "dark matter" of the exposome.